Social Welfare at The Grassroots and Contributions to National Development - Jeremiah, Ugwuoke Paulinus (Advances in Social Sciences Research Journal, 2021)
Globally, social problems are taking different dimensions, which keep evolving. Approaches to tackle these problems cannot only rely on improved economic power and privileges, whereby some global citizens cannot participate economically. This could be because of failed biological organs, weak institutions, or social disorganization. The consequences manifest in poverty, mortality, and vulnerability. While it is important for societies to develop economically, it is likewise important that they develop socially, by inclusion and social security. This is the essence of social welfare, as gaining increased attention across the globe. This paper looks at the concepts of social welfare and social development across continents and argues its importance to the achievement of sustainable development goals, especially for developing nations like Nigeria. It relies on a traditional review of the literature and a framework of models of welfare put forward by Titmus to include the residual, achievement-performance, and institutional models.